Vulnerability of Road Pavements to Climate Change in Abia and Imo States of Nigeria (Nigerian Journal of Technology, 2021)
Around the world today, road pavement is increasingly vulnerable and Southeast Nigeria is no exception. To this end, the Delphi technique is used in this study to ascertain experts opinions in order to identify and prioritize road pavements vulnerable to climate change in Abia and Imo states of Southeast Nigeria. As a measure of stability, standard deviation of two rounds of questionnaire responses was used to assess the level of convergence of opinions of 10-member Delphi panel. The Delphi panel achieved acceptable level of agreement at threshold values of standard deviation = 0.10 for stability and mean = 0.20 for consensus. Out of 14 federal roads considered in the study, 1 road had high vulnerability status, 5 roads had medium vulnerability status, 5 roads were rated low vulnerability and 2 roads were rated very low vulnerability. The only highly vulnerable road is from Abia state. This study has shown that the vulnerability of road pavements to climate change can be assessed comprehensively using collective and subjective judgement in the form of Delphi technique. Government should therefore apply adaptive maintenance plans that reflect the relative vulnerability rating of these roads.http://dx.doi.org/10.4314/njt.v40i1.2